Development Of A Chronological Life Span Assay For Ageing Studies In Saccharotnyces Cerevisiae - Ong, Tee Gee (2019)
The Saccharomyces cerevisiae. chronological life span (CLS) is the length of time that yeast cells survive in a non-dividing state. In the laboratory, CLS is typically measured by its optical density at the post-diauxic phase that begins approximately two days after initial inoculation. In this study, the development of a CLS assay on a 96-well microplate with different yeast strains and growth parameters (media and time) were carried out. After the evaluation of four different strains, yeast strain BY25929 was found to be the most suitable in tenns of growth for the CLS assay. A total of 24 ageing-related proteins were selected for assessment in the CLS assay.